Democracia, participação, autonomia: sobre a direção das escolas públicas - Lima, Licínio C. (2018)
Based on three theoretical dimensions that have emerged during the democratization process of school’s governance since the 25th of April 1974 revolution – election, collegiality, decision-making power ¬– the text offers a sociological interpretation of the situation of Portuguese schools till the present moment. Different combinations and intensity in the referred dimensions resulted in different periods: the self-government and active participation period, the formal democratic period under collegial bodies but a centralized administration, and the last period influenced by the rhetoric of school autonomy under the executive leadership of directors, although largely controlled by the central powers of the ministry of education. ¬